Design of continuous high‐efficiency broadband linear power amplifier using two‐tone signal analysis. Issue 1 (30th September 2019) - Qi, Tian; He, Songbai; Haider, Muhammad F.
Abstract: In this article, a novel method to design broadband linear power amplifier (BL‐PA) is presented. By adding the image parts for harmonics and intermodulation products (HIMPs), a suboptimal solution of efficiency and linearity in continuous frequencies can be achieved at a broadband to improve the efficiency and linearity performance of the BL‐PA. For verification, a BL‐PA operating 3.2‐3.8GHz is designed and the performances are assessed in multi modes.